RUSSIAN POET WITH AN UZBEK HEART - Abdurasulova Maftuna; Azimova Nigina; Yuldasheva Salomat (Journal of new century innovations, 2022)
Annotation: This article is about a Russian poet who spent his entire life working alongside the people of Uzbekistan and making a significant contribution to their development. He was born and raised there. The page includes information about the famous author and poet Alexander Feinberg’s life and creative legacy in addition to his original viewpoints.